Socially inclusive climate information services in Kenya: Mid-year report 2023 - Miriti, Philip; Bullock, Renee (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report summarizes three activities that were implemented to support socially inclusive scaling of climate information services (CIS). These activities included a workshop, radio programs and field visits. A workshop titled ‘Strengthening climate networks to support community capacities’, two piloted radio programs and field visits to climate observers are described. Collectively, these activities build capacity and learning with and among climate networks.